Modal Analysis of Two Stage Helical Gear Mining Reducer based on ANSYS Workbench - Lin Qiang; Dong Bin (Jixie chuandong)
The two stage helical gear reducer is widely used in different reduction occasions,of which the mode will directly affect the dynamic characteristics of the whole system. Based on the modal analysis theory,taking both the characteristic of the two stage helical gear deceleration system and the specific conditions into consideration,the geometry model of the gear transmission system is established by using the Solid Works,and it is imported into ANSYS Workbench by the seamless connection channel. After that,the finite element modal analysis with actual load and rotational speed is accomplished in a new loading approach,the low order natural frequency and the main vibration type of the gear transmission system is obtained,and the relative torsional vibration of gears is particularly analyzed. Comparing with non prestressed state modal analysis,the results suggest that the prestress of the gear transmission system has a great impact on the modal,the level of which is highly relative to the structural stiffness of gear.